2018
DOI: 10.1111/jocn.14507
|View full text |Cite
|
Sign up to set email alerts
|

It’s like balancing on a slackline—A description of how adults with congenital heart disease describe themselves in relation to physical activity

Abstract: Given the diverse relationship with physical activity, nurses have to further investigate the patients' relationship with physical activity, to support a healthy lifestyle. Nurses and allied health professionals should offer individualised exercise prescriptions and education about suitable physical activities in relation to physical ability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…They also found appropriate levels to be physically active. A recent study showed that adults with CHD described themselves as 'being a realist -adapting to physical ability', 19 and the present study shows that attitudes towards oneself might be an aspect of that statement. On the contrary, selfconfidence could also be seen as a barrier as some had set unrealistic goals that led to not being able to finalise the activity.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…They also found appropriate levels to be physically active. A recent study showed that adults with CHD described themselves as 'being a realist -adapting to physical ability', 19 and the present study shows that attitudes towards oneself might be an aspect of that statement. On the contrary, selfconfidence could also be seen as a barrier as some had set unrealistic goals that led to not being able to finalise the activity.…”
Section: Discussionsupporting
confidence: 62%
“…Even if the description of the analysis process seems linear, there has been movement back and forth between the whole and the part of the text including subcategories and categories. 19…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,[30][31][32] This reduced physical activity may be due in part to restrictions imposed by the child's cardiologist, parents, teachers/coaches, and/or themselves, [33][34][35] as well as numerous perceived barriers by the youth themselves. 5,[36][37][38] Fortunately, clinical recommendations have shifted from one of activity restriction to activity promotion in the CHD population. 39 Importantly, youth with CHD often have poor self-efficacy towards physical activity, 40 which itself is an important predictor of physical activity participation.…”
Section: Discussionmentioning
confidence: 99%